QTAIM and IRC studies for the evaluation of activation energy on the C=P, C=N and C=O Diels-Alder reaction - Imad Hammoudan; Samir Chtita; Driss Riffi-Temsamani (Heliyon, 2020)
In Diels-Alder reaction of 1,3-butadiene with hetero-dienophiles, the substitution of a carbon by a heteroatom as N, O and P on the dienophile decreases the activation energy, particularly for the phosphorus. All these reactions are concerted, proven by the DFT/B3LYP method using the cc-pVDZ basis. The intrinsic reaction coordinate (IRC) analysis confirms concerted reaction and the Quantum Theory of Atoms in Molecules (QTAIM) analysis shows that there are critical points BCP in the transition state structures with positive values for the interaction links.